A crítica de Wittgenstein a Russell: uma possível defesa de Russell - Saran, Lucas Antonio (2021)
The goal of this work is presenting Bertrand Russell’ thought from the unfinished 1913 manuscript, and debate the consequences of the criticism that Wittgenstein directed to some central points of that thought. Considering that goal, the discussions of this thesis will try to answer the following questions: is there any currentness in Theory of knowledge? To what point is Russell's thought able to resist to the criticism from Wittgenstein? What themes did Russell's thought abandon? What themes from Russell's thought (of 1913) remain important to our reflection? Trying to adress those questions, the present work will use two argumentative lines. The first of those lines takes the following assumption: the mature thought from Russell ‒ which beginning is the paper On propositions: what they are and how they mean ‒ keeps its currentness. From that assumption, the first argumentative strategy will be: without disregarding the relevance of Russell's work (from 1913) to a series of thinkers, this work will try to show the thematic continuity between Theory of knowledge to the mature thought from Russell, and to highlight the fact that, that book is part of a broader project that runs through a big part of Russell's production. Besides of that argument, this work will try to show some difference between Russell's and Wittgenstein's philosophical projects, because, if it is possible to verify that kind of difference, it's, at least, plausible to claim that Russell's project couldn't be totally assessed with ground at Wittgenstein's project